Analisis Nilai Perjuangan dalam Film Jembatan Pensil Disutradarai Oleh Hasto Broto dan Implikasinya Terhadap Pembelajaran Sastra Di SMP - Beby Auliya; Yuliati Eka Asi; Lazarus Linarto; Albertus Purwaka; Misnawati Misnawati (Universitas Palangka Raya, 2024)
This research aims to describe the values of struggle contained in a film and find out the implications for literature learning in junior high schools. This research focuses on the values of struggle, willingness to sacrifice, unity, respect, patience and the spirit of never giving up, and cooperation. This research uses a qualitative approach, a research approach in which data is collected in the form of words, images, and not numbers. A qualitative approach is used to describe the value of struggle in the film Pencil Bridge directed by Hasto Broto and its implications for literature learning in junior high schools. The data source for this research is the film Pencil Bridge, directed by Hasto Broto. Researchers found 53 values of struggle in the film Pencil Bridge and have outlined their implications for literature learning in junior high schools. The value of struggle that is most often found is the value of struggle of respect consisting of 16 data, followed by the value of struggle for being willing to sacrifice consisting of 14 data, and the value of struggle for patience and the spirit of never giving up consisting of 10 data, while the value of struggle that is least found is the value of the cooperative struggle consists of 8 data and the value of the united struggle is found in 5 data. The film Pencil Bridge is suitable to be used as a medium for teaching literature in junior high schools because the film Pencil Bridge, directed by Hasto Broto, contains exemplary values, especially the value of struggle.